QUALITY AND COST ANALYSIS FOR DENGUE FEVER BPJS PATIENTS AT RSIA ZAINAB - Alifa Khairunisa Indra, Karina
The health insurance payment scheme from the government between the insurance, BPJS Kesehatan, and the hospital is the based on the Indonesia Case Base Groups (INA CBGs). INA CBGs are standard rates that have been determined by National Casemix Center as a bill to the government for handling BPJS patients. With the implementation of this scheme, there are some cases where the actual hospital cost is lower than the INA CBGs rates so that hospitals can earn surplus, but there are also cases where actual hospital cost are higher than the INA CBGs rates so that hospitals suffer deficit. In this study, an analysis of the difference between hospital costs and INA CBG rates was performed. The method is carried out using Statistical Process Control where with control charts, the data is processed to obtain data that shows the hospital standard or in-control process. Afterward, the data that has indicated as a stable process is analyzed with Capability Analysis to determine whether the hospital is capable to carry out the process in accordance with the determined INA CBGs. This research was done at Zainab RSIA specifically for dengue fever. The results of the analysis, the hospital suffer a big loss from this scheme. Hospital is indicated to be incapable of adjusting the cost of handling patients with INA CBGs. This is shown by the calculation of defects that occurs for BPJS first class is 97%, BPJS second class is 95%, and BPJS third class is 85%. Further research is needed to analyze whether similar problems occur in other hospitals. If many hospitals experience similar issues, BPJS needs to re-evaluate INA CBGs rates because of the huge losses suffered by the hospital and the low Capability Index that reach negative value of the hospitals against the rates that have been determined.